The Need to Help : The Domestic Arts of International Humanitarianism - Malkki, Liisa H. (Liisa Helena) (Book collections on Project MUSE., 2015)
In this ethnography Liisa H. Malkki reverses the study of humanitarian aid, focusing on aid workers rather than aid's recipients. She shows how aid serves the needs of its recipients and providers.